International Conference on Transportation and Development 2022. selected papers from the International Conference on Transportation and Development 2022, Seattle, Washington, May 31-June 3, 2022 - Wei, Heng (Civil engineer) (American Society of Civil Engineers, 2022)
The sixth volume of the proceedings for the International Conference on Transportation and Development 2022, held in Seattle, Washington, May 31-June 3, 2022. This collection contains 17 peer-reviewed papers on transportation infrastructure systems. Topics include: asset management; risk assessment; economic analysis; and forecasting.
Sponsored by the Washington State Department of Transportation and the Transportation & Development Institute of the American Society of Civil Engineers.
Keywords: Transportation -- Management -- Congresses.; Infrastructure (Economics) -- Congresses.; Transportation -- Cost effectiveness -- Congresses.; Risk assessment -- Congresses.; elektronické knihy; electronic books